A handbook on Legal Languages and the quest for linguistic equality in South Africa and beyond - Docrat, Zakeera; Kaschula, Russell H; Ralarala, Monwabisi K (African Sun Media, 2021)
A handbook on Legal Languages and the quest for linguistic equality in South Africa and beyond is an interdisciplinary publication located in the discipline of forensic linguistics/ language and law. This handbook includes varying comparative African and global case studies on the use of language(s) in courtroom discourse and higher education institutions: Kenya; Morocco; Nigeria; Australia; Belgium Canada and India. These African and global case studies form the backdrop for the critique of the monolingual English language of record policy for South African courts, the core of this handbook, discussed in relation to case law and the beleaguered legal interpretation profession. This handbook argues that linguistic transformation and decolonisation of South Africa’s legal and higher education systems needs to be undertaken where legal practitioners are linguistically equipped to litigate in a bilingual/ multilingual courtroom that enables access to justice for the majority of African language speaking litigants, enforcing their constitutional language rights.